2017
DOI: 10.1111/andr.12425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone supplementation therapy on lipid metabolism in hypogonadal men with T2DM: a meta‐analysis of randomized controlled trials

Abstract: Testosterone supplementation may be effective for the treatment of hypogonadism in men with type 2 diabetes mellitus (T2DM), but the evidence from randomized controlled trials (RCTs) is inconclusive. We aimed to systematically summarize results from intervention studies and assess the effects of testosterone supplementation therapy (TST) on lipid metabolism in RCTs of hypogonadal men with T2DM by meta-analysis. PubMed, Embase, and Cochrane Library databases were searched for studies reporting the effect of TST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The authors concluded that the clinical significance of these changes is uncertain (Mohler et al ., 2018). A recent meta‐analysis of clinical studies of testosterone treatment in hypogonadal men (defined as total testosterone < 12 mmol/L) with T2DM included seven studies (total n = 612 men), 5 of which were RCTs (Zhang et al ., 2018). Again, a slight reduction in total cholesterol (−0.17 mmol/L) was reported, but in contrast to the T‐trials, testosterone treatment was associated with a significant reduction in triglyceride concentrations (−0.32 mmol/L).…”
Section: Metabolic Impact Of Testosterone Treatment In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the clinical significance of these changes is uncertain (Mohler et al ., 2018). A recent meta‐analysis of clinical studies of testosterone treatment in hypogonadal men (defined as total testosterone < 12 mmol/L) with T2DM included seven studies (total n = 612 men), 5 of which were RCTs (Zhang et al ., 2018). Again, a slight reduction in total cholesterol (−0.17 mmol/L) was reported, but in contrast to the T‐trials, testosterone treatment was associated with a significant reduction in triglyceride concentrations (−0.32 mmol/L).…”
Section: Metabolic Impact Of Testosterone Treatment In Clinical Trialsmentioning
confidence: 99%
“…Again, a slight reduction in total cholesterol (−0.17 mmol/L) was reported, but in contrast to the T‐trials, testosterone treatment was associated with a significant reduction in triglyceride concentrations (−0.32 mmol/L). Effects on HDL and LDL cholesterol were not significant in this meta‐analysis (Zhang et al ., 2018). In the aforementioned meta‐analysis by Corona, if only men with a baseline testosterone < 12 nmol/L were considered, similar reductions in total cholesterol (−0.35 mmol/L) and triglycerides (−0.22 mmol/L) were observed, and again, no effect on HDL or LDL cholesterol (Corona et al ., 2016).…”
Section: Metabolic Impact Of Testosterone Treatment In Clinical Trialsmentioning
confidence: 99%
“…Numerous studies have documented that androgen deficiencies and dysregulation of iron homeostasis are common features observed in obese men [1][2][3]. In Taiwan, one in two men is either overweight or obese [4], and one-fourth of Taiwanese men have an androgen deficiency (24.1%) (total testosterone (T) of <300 ng/dL or free T of <5 ng/dL) [5] and iron overload (21.5%) (serum ferritin>300ng/mL) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of TRT on HDL concentration yielded conflicting result with either a decrease [152] or no changes [102,153]. Other investigators observed an increase in concentration of HDL level after testosterone administration [154]. In a recent study on the effects of TRT on lipid metabolism in hypogonadal men with T2DM, it has been hypothesized that because the relationship between lipid metabolism and artherosclerosis are unequivocal, TRT, which ameliorates lipid metabolism, may decrease the morbidity and mortality of CVD in hypogonadal men with T2DM by preventing atherogenesis [155].…”
Section: Testosterone Replacement Therapy In Cvd Patientsmentioning
confidence: 99%